No god but man: on race, knowledge, and terrorism - Husain, Atiya (Global insecurities, 2025)
"Atiya Husain's No God but Man explores discourses around Muslims and racialization following the 9/11 attacks and the ensuing War on Terror. Husain uses the FBI's "most wanted" program, specifically the "most wanted terrorist" list, as an organizational centerpiece and public archive to understand constructions of race. Unlike other "most wanted" posters, descriptions on the "most wanted terrorist" list noticeably lack race as a category. In this way, Husain argues that the FBI considers these people, the majority whom are Muslim, as "raceless." Throughout the book, Husain utilizes an array of case studies, beginning with the work of Adolphe Quetelet, who was credited by former FBI director J. Edgar Hoover for the FBI's identification practices as well as the case of Assata Shakur, a former colleague of Malcom X and the only woman on the most wanted terrorist list. As a Black woman who was a Sunni Muslim in the 1970s, Shakur's case provides a unique scenario for Husain to explore how the FBI racializes both Muslims and Black Americans; and the creation of the most wanted terrorist list specifically and examines the "raceless" Muslim majority. No God but Man makes a bold intervention in the sociology of race, Black studies, and critical Muslim studies"--